Bioenergy and agriculture: Promises and challenges: Brazil's experience with bioenergy - Moreira, José Roberto (International Food Policy Research Institute, 2006)
Brazil is the world’s largest producer of ethanol, a biofuel used mainly in automobiles as an additive or alternative to gasoline. In the mid-1970s the country undertook a major program to produce ethanol, and since then the industry has had both successes and failures. Although Brazil’s program was criticized as being uneconomic during periods of low oil prices, the ethanol industry today is recognized as an efficient sector that brings substantial benefits to the Brazilian economy. All Brazilian ethanol is produced from sugarcane through the fermentation of sugars contained in sugarcane juice. In the 2005/06 growing season, Brazil harvested about 400 million metric tons of sugarcane on 5.5 million hectares (all tons in this brief are metric tons). Three hundred and thirty privately owned sugar mills each process an average of 1.2 million tons per year. The by-products, bagasse (residues from the sugar manufacturing process) and barbojo (tops and leaves remaining from harvesting), are generally burned. Bagasse in particular is traditionally burned in boilers and used as a source of heat and electricity for sugar/ethanol processing, as well as in other agroindustries, whereas barbojo is burned in the field, yielding no energy value.